Evaluating the Use of In‐Well Heat Tracer Tests to Measure Borehole Flow Rates. Issue 4 (5th November 2015) - Sellwood, Stephen M.; Hart, David J.; Bahr, Jean M.
Abstract: Recent research has demonstrated the use of in‐well heat tracer tests monitored by a fiber optic distributed temperature sensing (DTS) system to characterize borehole flow conditions in open bedrock boreholes. However, the accuracy of borehole flow rates determined from in‐well heat tracer tests has not been evaluated. The purpose of the research presented here is to determine whether borehole flow rates obtained using DTS‐monitored in‐well heat tracer tests are reasonable, and to evaluate the range of flow rates measureable with this method. To accomplish this, borehole flow rates measured using in‐well heat tracer tests are compared to borehole flow rates measured in the same boreholes using an impeller or heat pulse flowmeter. A comparison of flow rates measured using in‐well heat tracer tests to flow rates measured with an impeller flowmeter under the same conditions showed good agreement. A comparison of in‐well heat tracer test flow rate measurements to previously‐collected heat pulse flowmeter measurements indicates that the heat tracer test results produced borehole flow rates and flow profiles similar to those measured with the heat pulse flowmeter. The results of this study indicate that borehole flow rates determined from DTS‐monitored in‐well heat tracer tests are reasonable estimates of actual borehole flow rates. In addition, the range of borehole flow rates measurable by in‐well heat tracer tests spans from less than 10 −1 m/min to approximately 10 1 m/min, overlapping the ranges typically measurable with an impeller flowmeter or a heat pulse flowmeter, making in‐well heat tracer testing a versatile borehole flow logging tool.